Effect of Supportive Midwifery Care in Primiparous on Post-Traumatic Stress Disorder and Fear of Childbirth in Labour - Zeynep Bal; Tuba Uçar (Mardin Artuklu University, 2024)
Introduction: This study was conducted to determine the effect of supportive midwifery care in primiparous on posttraumatic stress disorder and fear of childbirth in labour.Methods: The study was conducted in the delivery room of a maternity hospital in eastern Turkey. The data were collected between January and November 2018. This study is a quasi-experimental study, in which pregnant women were sampled from the relevant population using the non-probability random sampling method. The sample consisted of 164 women, including 82 in the experimental group and 82 in the control group. The women in both groups were asked to complete a personal information form and the Wijma Delivery Expectancy/Experience Questionnaire (W-DEQ) Version A. Those in the experimental group received midwifery support during labour. The women in both groups were then given the Wijma Delivery Expectancy/Experience Questionnaire Version B and the Impact of Event Scale-Revised 6-8 hours after childbirth.Results: The mean prenatal W-DEQ version A score was 47.15±19.68 in the experimental group and 63.23±23.10 in the control group. There was a significant difference in mean scores between the groups (p